Improving crop water productivity under stressed environment - Sharma, Bharat R. (2011)
The global water resources are stressed due to high population pressure, demand for more and better food, over-exploitation of the surface and groundwater resources, urgent need to make provisions for the environmental services, and meet the expanding demands of non-food sectors. As a consequence, pollution is increasing and rivers are drying up because of greater agricultural production and water consumption; land and water resources are being stressed through erosion, salinization, nutrient depletion and the intrusion of seawater; and groundwater levels are declining rapidly in densely populated areas of North Africa, North China, India, and Mexico because of overexploitation. Increasing water withdrawals and water depletion for irrigation under such stressed conditions further aggravates the severity of the already stressed environments. Unfortunately, in most developing countries, water infrastructure and management institutions have been slow to build or improve capacity and adapt to new issues and conditions. Additionally, the world is facing the new challenges of climate change affecting temperature and precipitation patterns hitting the poor and the rainfed farmers more severely; urbanisation increases demand for water and generates more wastewater; higher energy prices increase the cost of pumping water; and more attention is being given to ecosystem services of water.